2017
DOI: 10.1021/acs.jctc.7b00797
|View full text |Cite
|
Sign up to set email alerts
|

Intricacies of van der Waals Interactions in Systems with Elongated Bonds Revealed by Electron-Groups Embedding and High-Level Coupled-Cluster Approaches

Abstract: Noncovalent interactions between molecules with stretched intramonomer covalent bonds are a fascinating, yet little studied area. This shortage of information stems largely from the inability of most of the commonly used computational quantum chemistry methods to accurately describe weak long-range and strong nondynamic correlations at the same time. In this work, we propose a geminal-based approach, abbreviated as EERPA-GVB, capable of describing such systems in a robust manner using relatively inexpensive co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(65 citation statements)
references
References 85 publications
4
61
0
Order By: Relevance
“…We have already observed a similar behavior (i.e., attraction growth accompanying a bond stretching) for other vdW complexes in Ref. [22], where we explained it by the increased polarizability of the electrons in the stretched bond region and an electron density buildup in the region between monomers. This causes a rise in both Pauli repulsion and dispersion interaction, which explains the existence of a minimum in the interaction energy along the F 2 bond stretch mode.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…We have already observed a similar behavior (i.e., attraction growth accompanying a bond stretching) for other vdW complexes in Ref. [22], where we explained it by the increased polarizability of the electrons in the stretched bond region and an electron density buildup in the region between monomers. This causes a rise in both Pauli repulsion and dispersion interaction, which explains the existence of a minimum in the interaction energy along the F 2 bond stretch mode.…”
Section: Resultssupporting
confidence: 80%
“…Already in [22], we have shown that EERPA-GVB describes accurately the dispersion-dominated systems. Here, we reaffirm this statement, adding that for this type of systems EERPA-GVB tends to be on par or even more accurate than SAPT [11,44] computations (see Table 1).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Interactions between genuinely multireference molecules require capturing a delicate balance between intermonomer dynamical correlation and intramonomer static correlation and are subject of intense research. For example, the stretching of a covalent bond in one of the interacting molecules has been shown to first enhance and then suppress the noncovalent binding, and single‐reference SAPT provides useful insight into this behavior up to a certain point on the stretching curve . Beyond that point, a truly multireference SAPT formalism is required, a goal that has not been fully accomplished yet.…”
Section: Extending the Applicability Of Saptmentioning
confidence: 99%